A zero power current and frequency sensor for smart grid applications. (1st September 2022) - Aragonez, Omar; Jackson, Nathan
Abstract: Obtaining real time feedback on the amplitude and frequency of current flowing through power lines is of significant importance to smart grids. This paper investigates the use of a zero power multifunctional device (sensor and energy harvester) to solve this challenging problem. The passive device combines a piezoelectric cantilever with a hard magnet mass in order to couple the AC magnetic field from the power line to the device to generate an oscillating kinetic force at the frequency of the current. The proposed device is passive, but the transmission of the data requires the use of wireless sensor nodes, which requires power. The piezoelectric cantilever acts as both a passive sensor and a kinetic energy harvester to power the wireless sensor nodes. This study investigates the effects on both the sensor sensitivity and energy harvesting power density as a function of the type of wire (stranded vs solid wires), stiffness of the cantilever, and pull strength of the magnet for high current applications. The results demonstrate that stranded wires have a slight reduction in sensitivity from 1.12 V A −1 to 0.98 V A −1 for solid and stranded wire. The stiffness of the cantilever also affects the sensitivity and energy harvesting performance, where stiffer beams resulted in high power density and sensitivity. Increasing the magnet thickness and pull strength resulted in increased power density and bandwidth but it also effects the optimal spatial location of the magnet in relation to the wire. The device was also validated as a frequency sensor with a resolution of <1 Hz, and could be further optimized in the future. The results of this study validate the potential use of the device as a multifunctional sensor/energy harvester for smart grid applications.